The Relationship of Knowledge with People's Attitudes Towards People with Mental Disorders - Pandi, Meysi Tessa; Astuti, Widya; Gaib, Juritno Harmi (Bantayang Omni Cendekia, 2025)
Background: People with mental disorders often receive greater stigma and discrimination from the surrounding community than individuals who suffer from other medical illnesses, The society's view of people with mental disorders has an impact on people with mental disorders. In this condition, the community should play a role as one of the support systems for people with mental disorders. Objective: The purpose of this study is to analyze and identify the relationship between knowledge and people's attitudes towards people with mental disorders. Methods: The type of research used in this study is simple Random Sampling, with a cross sectional research approach which means taking momentary measurements and data being analyzed using the chi-square test with a sample of 36 respondents. Results: The results of this study found that the public's knowledge was mostly good as many as 21 respondents, poor knowledge as many as 15 people and the community's attitude towards people with mental disorders was mostly positive for 21 respondents and negative attitudes amounted to 15 respondents. Conclusion: The results of the chi-square statistical test obtained a value of p = 0.000 or p < 0.05. This means that there is a relationship between knowledge and people's attitudes towards people with mental disorders.